The porous structure of activated carbon-based on waste coffee grounds - Sklepova, S.-V. S.; Gasyuk, I.M.; Ivanichok, N.Ya.; Kolkovskyi, P.I.; Kotsyubynsky, V.O.; Rachiy, B.I. (Physics and Chemistry of Solid State, 2022)
Nanoporous carbon materials (NCM) are used to prepare supercapacitor (SC) electrodes. The high specific energy parameters of SC are closely related to the physical and electrochemical characteristics of NCM. NCM with a highly developed surface area and controlled pore size distribution are obtained by chemical and thermal activation of carbon containing precursors. In our work we propose a thermochemical method of obtaining NCM with a high specific surface area. NCM were obtained by thermochemical activation of potassium hydroxide waste coffee grounds (WCG).